Employee associations with R&D investment, firm performance, disruption risk, and supply chain performance during the COVID-19 pandemic: A multiple mediational model - Sulehri, Numair Ahmed; Ullah, Naeem; Maroof, Zaib; Uzair, Ali; Murtaza, Abroo; Irfan, Muhammad (Frontiers in Environmental Science, 2023)
Purpose: To timely manage supply chain disruptions, experts have focused their attention on the impact of COVID-19 on industries worldwide. Epidemic outbursts are a specific supply chain risk with long disruption propagation, disruption persistence, and high uncertainty. This study aimed to investigate the role of R&D investment and firm performance in mediating the relationship between disruption risk and supply chain performance in Pakistani manufacturing industries and supply chain employees during the recovery phase of the COVID-19 pandemic via the application of the dynamic capability theory. Methodology: From 21 July 2020 to 23 August 2020, 318 employees from supply chains of manufacturing industries in Rawalpindi and Islamabad, Pakistan, participated in this cross-sectional online web-based survey. The four standard research scales were used to examine the research and development, disruption risk, firm, and supply chain performance. The response link was distributed to respondents via Facebook, WhatsApp, and email. The study analyzed the data using structural equation modeling and a partial least squares technique. Results: The study’s findings suggest that disruption risk, research and development investment, and firm performance all improve supply chain performance, but the mediation effect is unsupported by the data. These measures help plan a better supply chain in the face of disruption risk. They provide one of the timely empirical conclusions on the role of R&D investment in mitigating risk disruptions and improving supply chain performance.